Georgia : Poverty Reduction Strategy Paper Progress Report- Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The Joint Staff Advisory Note (JSAN) on the Poverty Reduction Strategy Paper Progress Report on Georgia evaluates the strengths and weaknesses of the poverty reduction objectives and strategies. Participation of stakeholders in the poverty reduction strategy process has been satisfactory. The growth basis for the strategy needs to be strengthened through the construction of a financially viable power grid with reliable supply of electricity to all regions of Georgia. Governance and public service delivery improvements need to be promoted through the further empowerment of civil society.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet